Multiple-trellis-coded unitary space-time modulation in Rayleigh flat fading. - Zhenyu Sun (IEEE Transactions on wireless communications)
We propose and investigate a multiple-trellis-coded unitary space-time modulation (MTC-USTM) for a Rayleigh-flat-fading channel, where k≥2 unitary space-time signal blocks are assigned to a single branch in the trellis. We have also evolved design criteria which are aimed at minimizing the pairwise error-event probability (PEP) and a partitioning scheme for the k-fold Cartesian product of the UST signal set for MTC-USTM. We demonstrate through simulations as well as theoretical analysis that MTC-USTM can produce superior bit-error probability performance over the trellis-coded USTM (single signal per branch) of the same information rate and number of states, especially in the region of high signal-to-noise ratio.